Evaluation of the in vivo fate of ultrapure alginate in a BALB/c mouse model. (15th June 2021) - A, Anitha; Fletcher, Nicholas L.; Houston, Zachary H.; Thurecht, Kristofer J.; Grøndahl, Lisbeth
Graphical abstract: Table of contents Alginate remains in blood for at least 14-days and accumulates in spleen mediated by macrophages. Highlights: A 14-day biodistribution study of ultrapure alginate in a mice model confirmed the clearance of a portion of the polymer. Liver and spleen uptake of alginate was observed up to 48 h using PET imaging. Liver and spleen uptake observed up to 14 days using fluorescence imaging. Using MacGreen mice confirmed spleen uptake through interaction with macrophages. Abstract: The linear anionic polysaccharide alginate (ALG) has been comprehensively studied for biomedical applications, yet thus far the in vivo fate of this polymer has not been explored in detail. The current study therefore evaluates the biodistribution of ultrapure ALG (M/G ratio ≥ 0.67 with a measured Mw of 530 kg/mol and polydispersity index; PDI of 1.49) over a 14-day period in BALB/c mice. The biodistribution pattern over 2-days after sample administration using PET imaging with 64 Cu-labelled ALG showed liver and spleen uptake. This was confirmed by the 14-day biodistribution profile of cyanine 5-labelled ALG from in vivo and ex vivo fluorescence imaging. Using MacGreen mice confirmed the uptake of the ALG by macrophages in the spleen at the 2-day time point. This extended biodistribution study confirmed the clearance of only a portion of the administered ALG biopolymer, but also uptake by macrophage populations in the spleen over a 14-day period.